First mesocosm experiments to study the impacts of ocean acidification on plankton communities in the NW Mediterranean Sea (MedSeA project). (15th February 2017) - Gazeau, F.; Sallon, A.; Maugendre, L.; Louis, J.; Dellisanti, W.; Gaubert, M.; Lejeune, P.; Gobert, S.; Borges, A.V.; Harlay, J.; Champenois, W.; Alliouane, S.; et al.
Abstract: There is a growing international interest in studying the effects of ocean acidification on plankton communities that play a major role in the global carbon cycle and in the consumption of atmospheric CO2 via the so-called biological pump. Recently, several mesocosm experiments reported on the effect of ocean acidification on marine plankton communities, although the majority were performed in eutrophic conditions or following nutrient addition. The objective of the present study was to perform two mesocosm experiments in the oligo- to meso-trophic Northwestern Mediterranean Sea during two seasons with contrasting environmental conditions: in summer 2012 in the Bay of Calvi (Corsica, France) and in winter 2013 in the Bay of Villefranche (France). This paper describes the objectives of these experiments, the study sites, the experimental set-up and the environmental and experimental conditions during the two experiments. The 20-day experiment in the Bay of Calvi was undoubtedly representative of summer conditions in the Northwestern Mediterranean Sea with low nutrient and chlorophyll a concentrations, warm waters and high surface solar irradiance. In contrast, the winter experiment, which was reduced to 12 days because of bad weather conditions, failed to reproduce the mesotrophic conditions typical of the wintertime in this area. Indeed, a rapid increase in phytoplankton biomass during the acidification phase led to a strong decrease in nitrate concentrations and an unrealistic N and P co-limitation at this period of the year. An overview of the 11 other papers related to this study and published in this special issue is provided.